Re-writing international relations history and theory beyond Eurocentrism in Turkey - Çapan, Zeynep Gülşah (Global dialogues : developing non-Eurocentric IR and IPE, 2016)
This book tells a different story of International Relations by challenging disciplinary and theoretical boundaries from the Turkish perspective with the aim of creating a more connected and global International relations